(untitled) (Jurnal Teknologi (Sciences & Engineering), 2022)
A rhombic with unbalanced three-split in a passive micromixer is studied. This work aims to optimize micromixers' three-split rhombic design for chemical analysis through mixing index and pressure drop analysis. The optimization was obtained by varying the angle of the rhombic and the ratio of the sub-channel widths, including angles of 30°, 45°, 60°, 90° and widths of 150:100 μm, 200:100 μm, 250:100 μm, and 300:100 μm. The COMSOL Multiphysics was used to simulate the performance based on a three-dimensional Navier-Stokes equation with the working fluid model in the form of water in the advection-diffusion model. A parametric study was carried out to evaluate the effect of the geometric micromixer variable on the mixing performance for the Reynolds range of 10-120. The results show that a micromixer with an unbalanced triangular rhombic the structure with an angle of 30° and width of 200:100 μm on Re 120 achieve mixing efficiency at 0.91 with pressure drop 1700 Pa.